A P2X receptor-mediated nociceptive afferent pathway to lamina I of the spinal cord - Gu Jianguo G; Chen Meng (SAGE Publishing, 2005)
Abstract Of the six lamina regions in the dorsal horn of the spinal cord, lamina I is a major sensory region involved in nociceptive transmission under both physiological and pathological conditions. While P2X receptors have been shown to be involved in nociception, it remains unknown if P2X receptors are involved in nociceptive transmission to lamina I neurons. Using rat spinal cord slice preparations and patch-clamp recordings, we have demonstrated that the excitatory synaptic transmission between primary afferent fibers and lamina I neurons is significantly affected by ATP and α,β-methylene-ATP. The synaptic effects of them include the increases of the frequency of both miniature excitatory postsynaptic currents (mEPSCs) and spontaneous EPSCs (sEPSCs), and decreases of evoked EPSCs (eEPSCs). These effects were blocked by pyridoxalphosphate-6-azophenyl-2', 4'-disulfonic acid (PPADS, 10 μM) and suramin (30 μM). In the neurons for which ATP and α,β-methylene-ATP had effects on mEPSCs, sEPSCs and eEPSCs, capsaicin produced similar synaptic effects. Our results indicate that P2X receptors are expressed on many afferent fibers that directly synapse to lamina I neurons. Furthermore, these P2X receptor-expressing afferent fibers are capsaicin-sensitive nociceptive afferents. Thus, this study reveals a P2X receptor-mediated nociceptive afferent pathway to lamina I of the spinal cord and provides a new insight into the nociceptive functions of P2X receptors.